Implementation of School TV in Improving Teacher Creativity in Early Childhood Education - Tika Wijayanthi R; Sri Watini; Mega Hendrica; Farah Ayu Maulidina; Erlina; Mulyana Sukarni Putri (International Conferences on Early Childhood Education Proceedings, 2024)
Education is one of the key factors in shaping and developing student potential. The success of character education implies that learning is not necessarily seen from the perspective of the cognitive domain alone but how to balance the cognitive, affective, and psychomotor domains which ultimately realize the whole person. Emotional changes, teachers must selectively choose and determine the platform to be used in learning School TV can be used as an alternative media Implementation of School TV Media in Improving Teacher Creativity in Early Childhood Education. The method used in this study uses a qualitative approach, aiming to describe thoroughly and in depth the reality in the field. the location in this study was held at the Paud Institution in Serang City Banten and the subjects in this study were the Principal, school operators and teachers from paud institutions in Serang City Banten. From the results of the above research, it can be concluded that School TV has its own charm in increasing Teacher Creativity, so that they can create learning innovations and new modules. And also early childhood is protected from non-educational viewing, with the existence of school TV, children feel that their videos enter the TV like a TV at home.